Abstracts of the 20th Congress of the International Federation of Infection Control (IFIC2020) - Authors, Various (International Journal of Infection Control, 2020)
This Supplement contains abstracts for the 20th Congress of the International Federation of Infection Control, Belgrade, Serbia, March 11-14, 2020. Despite the cancellation of the Congress due to the COVID-19 pandemic, the conference organizers and IJIC recognize those presenters whose research was to be presented and are pleased to publish their abstracts